Letter (copy) : Spanish Civil War - Citrine, Walter, 1887-1983
010-0135-001 WMC/FEM/FP/416 Secretary's. 15th August, 1936. Mr. H.H. Elvin, National Union of Clerks, 17-20, Holborn Hall, Gray's Inn Road, W.C.1. Dear Mr. Elvin, Spanish Civil War. Thank you for your letter of the 14th August, with regard to the position in Spain, particularly the supply of war materials to the rebels. As this is a matter of joint policy, it is really one for the National Council of Labour to deal with, and the officers of the N.C.L. are keeping in very close touch with the position. Yours sincerely, General Secretary. 292/946/10/148